Method of Matrix Solution of System of Linear Algebraic Equations Using Programming Language (Texas Journal of Engineering and Technology, 2022)
This article mentions the use in Html environment. In addition, it was shown that interdisciplinary integration is important in preparing future programmers for professional activities.